Elevated Turbidity and the Nutrient Removal Capacity of Seagrass - Bulmer, Richard Hugh; Townsend, Michael; Drylie, Tarn; Lohrer, Andrew Martin (Frontiers in Marine Science, 2018)
Seagrass meadows provide a range of important ecosystem functions that can be influenced by anthropogenic pressures. Sediment loading from coastal land use mismanagement can elevate turbidity and reduce seabed light levels, thereby impacting seagrass primary productivity and meadow health. Less understood is the impact of elevated turbidity on the nutrient removal capacity of seagrass, which is a key ecosystem function. Here, we use in situ benthic chambers to show that elevated turbidity is associated with lower nutrient (NH4+) removal within intertidal seagrass meadows. Our results suggest that reductions in sediment loading to improve water clarity may increase the nutrient removal capacity of intertidal seagrass meadows influenced by light limitation. When quantifying important ecosystem functions such as nutrient removal by seagrass it is important to consider this context dependency.